2011
DOI: 10.2503/hrj.10.101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sensory Test, and Chemical and/or Physical Properties of Japanese Bunching Onion

Abstract: For characterization of chemical and/or physical taste evaluation of Japanese bunching onion (welsh onion), the relationship between sensory descriptions of pungency, sweetness and texture, and the chemical and/or physical properties were investigated. Pungency score of the fresh bunching onion and the amount of pungent precursors estimated by pyruvic acid production showed a strong positive correlation (r = 0.94**). Sweetness score of the heated bunching onion and brix value did not show a positive correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The palatability of soybean vegetable depends on the production of taste substances (i.e., free amino acids and sugars) and texture after boiling. As the palatability of rice, chestnut and Japanese bunching onion was reported to be positively correlated with free sugar content (Konishi et al, 1996;Sugimoto et al, 2004;Miyagi et al, 2011), the palatability of soybean vegetable with respect to sugar composition after boiling was investigated in this study. In the case of fresh soybean vegetable, sucrose was the main free sugar in all cultivars investigated, as previously reported by Masuda (2004).…”
Section: Discussionmentioning
confidence: 98%
“…The palatability of soybean vegetable depends on the production of taste substances (i.e., free amino acids and sugars) and texture after boiling. As the palatability of rice, chestnut and Japanese bunching onion was reported to be positively correlated with free sugar content (Konishi et al, 1996;Sugimoto et al, 2004;Miyagi et al, 2011), the palatability of soybean vegetable with respect to sugar composition after boiling was investigated in this study. In the case of fresh soybean vegetable, sucrose was the main free sugar in all cultivars investigated, as previously reported by Masuda (2004).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it was suggested that salt tolerance mechanisms of Wakegi from Okinawa might differ from those of Welsh onion and Wakegi from Nagasaki. Miyagi et al (2011) conducted sensory evaluation of Welsh onion, and demonstrated a strong positive correlation between free sugar content and palatability. In the case of Welsh onion and Wakegi from Nagasaki, salinity treatment with a seawater concentration of 10% effectively produced a higher content of sugars compared to the control plants not subjected to the treatment, which might lead to good palatability.…”
Section: Resultsmentioning
confidence: 99%
“…The mineral content of the 100% seawater used in this study was as follows (mg/100 mL): Na + : 942. Sugar content analysis The free sugar content was determined according to the method described by Miyagi et al (2011). Briefly, a 5 mm section of each plant (10 g) was refluxed in 100 mL of 85% ethanol (80℃, 60 min).…”
mentioning
confidence: 99%
“…The intensity of sweetness in D-glucose and fructose is different compared with that in sucrose. The intensities of sweetness in D-glucose and fructose are 0.65-fold and 1.25-fold greater, respectively, than the intensity of sweetness in sucrose (Miyagi et al, 2011). Therefore, we calculated the "degree of sweetness" for the evaluation of total sweetness using the mathematical formula stated below.…”
Section: Methodsmentioning
confidence: 99%